2024
DOI: 10.1007/s40122-024-00590-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Volumes of Ropivacaine for Pericapsular Nerve Group Block on Incidence of Quadriceps Weakness and Analgesic Efficacy Following Hip Arthroplasty: A Randomized Controlled Trial

Huaichang Wen,
Weihua Zhang,
Yi Wang
et al.

Abstract: Introduction The pericapsular nerve group (PENG) block has been shown to be an effective approach to alleviating pain and reducing the need for opioids among older adults following hip surgery, with possible motor-sparing effects. No reports to date, however, have described appropriate ropivacaine volumes for use in the context of PENG block. The present prospective randomized controlled study was thus developed to assess the quadriceps muscle strength and analgesic efficacy associated with PENG b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…It’s worth noting that we would like to draw the reader’s attention to recent findings in the field that may broaden the understanding of this article. Wen et al 4 conducted an important study to explore the appropriate volume of ropivacaine for peripheral nerve group (PENG) blockade after general anaesthesia in elderly people undergoing hip arthroplasty and concluded that the 20 mL 0.33% ropivacaine group had better motor function preservation than the 30 mL 0.33% ropivacaine group and better postoperative pain relief in the 20 mL and 30 mL volumes of 0.33% ropivacaine than in the 10 mL 0.33% ropivacaine group. It was concluded that the 20 mL 0.33% ropivacaine group had better preservation of motor function than the 30 mL 0.33% ropivacaine group and that the 20 mL and 30 mL volumes of 0.33% ropivacaine groups had better postoperative pain relief than the 10 mL 0.33% ropivacaine group.…”
Section: Dear Editormentioning
confidence: 99%
“…It’s worth noting that we would like to draw the reader’s attention to recent findings in the field that may broaden the understanding of this article. Wen et al 4 conducted an important study to explore the appropriate volume of ropivacaine for peripheral nerve group (PENG) blockade after general anaesthesia in elderly people undergoing hip arthroplasty and concluded that the 20 mL 0.33% ropivacaine group had better motor function preservation than the 30 mL 0.33% ropivacaine group and better postoperative pain relief in the 20 mL and 30 mL volumes of 0.33% ropivacaine than in the 10 mL 0.33% ropivacaine group. It was concluded that the 20 mL 0.33% ropivacaine group had better preservation of motor function than the 30 mL 0.33% ropivacaine group and that the 20 mL and 30 mL volumes of 0.33% ropivacaine groups had better postoperative pain relief than the 10 mL 0.33% ropivacaine group.…”
Section: Dear Editormentioning
confidence: 99%